Attitude and Perception of Oral Health Problems in Pregnant Women (Medical Forum Monthly, 2024)
Objective: The objective of this study was to assess attitude towards oral and dental health during pregnancy and to examine their self-care practices in relation to oral and dental health.Study Design: cross-sectional descriptive and analytical studyPlace and Duration of Study: This study was conducted at the Jinnah Medical & Dental College, Karachi from January 2013 to September 2013Materials and Methods: This was a cross-sectional descriptive and analytical study conducted at the Jinnah Medical & Dental College Karachi (JMDC). The study group comprised of 118 pregnant women attending the Jinnah Medical & Dental College OPD from January 2013 to September 2013 using convenience sampling method. A 15 item questionnaire was used, after it was pre-tested and validated. The data entry was done by the house officers of JMDC. Statistical analysis was done using SPSS version16.Results: 65% of the total patients were found to have dental caries on overall intraoral examination out of these 52% patients had pain on percussion. 44% of the patients presented with gingivitis and bleeding on probing while 21% presented with clinical periodontitis with mobility. 22.8% of the pregnant women presented with gingival enlargements out of which 13.55% had localized while 9.3% had generalized gingival enlargements. 62% of the pregnant women said they brush twice daily while 27% brush once daily only 3% women said that they brush their teeth occasionally. None of them did flossing. Only 10% of the women had regular dental checkups after every six months.Conclusion: This study observed the oral health care practices of the pregnant women. The study highlighted the lack of awareness of maintenance of oral health. Intensive oral and dental health education in pregnancy can lead to improved oral and dental health, and ultimately safe pregnancy outcomes.